Audit Tata Kelola Sistem Informasi Pada PT Pegadaian (Persero) Batam Pada Domain PO7, DS1 dan ME4 - Kartika Kartika; Amrizal Amrizal (Journal of Information System Research (JOSH), 2020)
PT Pegadaian (Persero) is an Indonesian financial sector BUMN that is engaged in goods pawning services. The purpose of the information system governance audit at PT Pegadaian (Persero) Batam Branch is to determine the level of maturity in the PASSION system. the system has been running well and then conducted an audit to find out whether the system used has been efficiently and effectively supporting business processes. This research focuses on performance measurement, and the method used in this study is the Cobit 4.1 framework which contains 3 subdomains, PO7, DS1, ME4. The results of this study the level of information system maturity in the PO7 domain with a value of 2.34, the DS1 domain with a value of 2.37, and at the ME4 domain with a value of 3.54. so the maturity level of PT Pegadaian (pesero) Bengkong Branch information system is an average of level 3 (Defined)